Prevalence and risk indicators of primary dentition malocclusion in Riyadh-Saudi Arabia using a new case definition: A cross-sectional study - Hoda M Abdellatif; Nozha Sawan; Amjad M Alabdulmohsen; Ghaida AlKheraif; Haifa AlKhonin; Amal Ali; Mona A Elkateb (Saudi Dental Journal)
Objectives: To determine the prevalence of primary dentition malocclusion and its linked risk indicators among a group of Saudi preschool children. Methods: A cross-sectional study was carried out on preschool children aged 3 to 5 years residing in Riyadh City, the capital of Saudi Arabia. The study sample included 709 Saudi children of both genders with complete primary dentition. Oral examination was conducted for children to assess the anteroposterior, transverse, and vertical dimensions, arch spacings, and oral habits. Results: The prevalence of malocclusion was 59.1% among the study participants. A deep overbite and increased overjet were found in 26.23 % and 25.11%, respectively. Arch space problems were reported, including missing primate spaces in 24.12%, missing developmental spacing in 27.93%, and crowding in 14.1%. An association between mothers aged 25 years and younger at childbirth was linked with their child's malocclusion in the primary dentition (p-value of 0.03). Conclusion: The prevalence of primary dentition malocclusion among a specific group of Saudi preschool children was significantly high. Increased overbite and overjet were the most prevalent occlusal discrepancies, followed by arch spacing problems. The younger mother's age at childbirth is significantly associated with her child's malocclusion. The study results can serve as a baseline for future investigations.